Can cardiac pressure-volume catheters improve urodynamic assessment? an ex-vivo proof-of-concept - Jahren, Silje Ekroll; Obrist, Dominik; Haenggi, Matthias; Burkhard, Fiona; Clavica, Francesco (Frontiers in Urology, 2023)
Aims: To explore the feasibility of using pressure-volume (PV) catheters for cystometry. These catheters are well-established in cardiovascular research for simultaneous pressure and volume measurements in the left ventricle.Methods: Urinary bladders with urethras were collected from domestic pigs for ex-vivo testing. Using a pump, bladders were filled up to 500ml at five different filling rates (15, 20, 25, 30, 35ml/min), and the resulting pressures and volumes were measured using a PV catheter. The bladder were compressed externally in three different areas (central, apex and outlet) to assess the PV catheter's ability to detect local changes in bladder volume.Results: Bladder pressure remained below 10cmH2O for all bladder filling rates. Volume measurements were compared with the volumes instilled by the pump (ground truth), proving high reproducibility and accuracy of the PV catheter measurements up to 400ml. Using the different sensing units of the PV catheter, local changes in bladder volumes could be identified and quantified.Conclusions: The main advantage of PV catheters, compared to existing technology used in urology (e.g. conventional urodynamic testing), is the possibility to i) simultaneously measure bladder pressure and volumes and ii) identify local changes in bladder volume (e.g. caused by non-voiding contractions). Both could be useful in the clinical setting to improve the diagnosis and treatment of the Lower Urinary Tract Dysfunction (e.g. overactive/underactive bladder).